Respon kebal nonspesifik ikan mas yang diberi imunostimulan ragi roti secara oral - Yanuar, Aditya P.; Manoppo, Henky (Universitas Sam Ratulangi, 2017)
The effect of baker’s yeast as immunostimulant on innate immunity of carp (Cyprinus carpio L) had been investigated. Fish was gathered from Freshwater Aquaculture Board (BBAT) Tatelu, Province of North Sulawesi. The fish were acclimatized for a week in 15 aquariua with a density of 25 fish/aquarium. After acclimatization the fish were fed pellet supplemented with baker’s yeast as immunostimulant at 0, 5, 10, 15 and 20 g / kg of feed for four weeks as much as 5%/body weight of fish/day with the frequency of feeding twice a day at 08.00 am and 16.00 pm . This study used Completely Randomized Design (RAL) with five treatments and each treatment had three replications. Immune parameters consisting of total leucocytes and phagocytosis activity were measured in the last week. After four weeks of feeding, the total leukocytes from the carp fed with the addition of baker’s yeast 10 g / kg of feed were significantly increased compared with the fish not being fed with the addition of bread yeast (p <0.01). Phagocytic activity of phagocyte cells from carp also increased significantly in fish fed pellet with the addition of 5 g of baker’s yeast / kg of feed (p = 0.01). In conclusion, the addition of baker’s yeast as immunostimulant in the diet at 5-10 g/kg of pellet can increase the nonspecific immune response of carp. Keywords: baker’s yeast, carp, nonspesific immune response, total leucocytes, phagocytosis activity